Reality Therapy/Choice Theory Today: An Interview with Dr. Robert E. Wubbolding - Klingler, Lacey; Gray, Neal D. (Canadian Journal of Counselling and Psychotherapy, 2015)
This article offers highlights from an interview with Dr. Robert E. Wubbolding, Director of the Center for Reality Therapy in Cincinnati, Ohio, USA. The article will focus on current applications for using reality therapy and choice theory. In particular, this interview addressed assumptions underlying reality therapy and choice theory, key concepts essential to theory and practice, the most important goals of reality therapy, major strengths from a diversity perspective, and a vision for the future of reality therapy.